2013
DOI: 10.5573/jsts.2013.13.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Impact Analysis of NBTI/PBTI on SRAM VMINand Design Techniques for Improved SRAM VMIN

Abstract: Abstract-Negative bias temperature instability (NBTI) and positive bias temperature instability (PBTI) are critical circuit reliability issues in highly scaled CMOS technologies. Index Terms-Negative bias temperature instability (NBTI), positive bias temperature instability (PBTI), SRAM V MIN , SRAM, SRAM cell stability, pulsed wordline, wordline control

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…It has been shown that by optimizing the cell design, eg., α ratio of the cell, proper mix of RM vs WM dominated devices and transistor process optimization, the drift can be controlled to a tolerable level [7]. It has also been shown that NBTI has a stronger impact on Vmin than PBTI [4,5]. Consequently, the memory minimum operating voltage (memory Vmin) has been demonstrated to increase over time to compensate the degraded memory static noise margin (SNM) as shown in Fig 6. Literature has also reported memory stability on process corners due to a word-pulse width effect at time-zero [8].…”
Section: Vmin Aging and Rtnmentioning
confidence: 90%
See 2 more Smart Citations
“…It has been shown that by optimizing the cell design, eg., α ratio of the cell, proper mix of RM vs WM dominated devices and transistor process optimization, the drift can be controlled to a tolerable level [7]. It has also been shown that NBTI has a stronger impact on Vmin than PBTI [4,5]. Consequently, the memory minimum operating voltage (memory Vmin) has been demonstrated to increase over time to compensate the degraded memory static noise margin (SNM) as shown in Fig 6. Literature has also reported memory stability on process corners due to a word-pulse width effect at time-zero [8].…”
Section: Vmin Aging and Rtnmentioning
confidence: 90%
“…There is plenty of published work which discusses the BTI impact on parametric or Vmin drift, including [4,5]. However, details regarding comprehensive protection against Vmin failures are very limited.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, the stress condition is removed and decreased the threshold voltage. The threshold voltage shift of MOSFET transistors due to BTI effects under static stress can be described by dc reaction and diffusion (R-D) model [2,14,18,21,22,31,32]. If the gate voltage of transistor is regularly flipped under alternative stress, the dc R-D model should be modified to an ac R-D model:…”
Section: Nbti and Pbti Modelsmentioning
confidence: 99%
“…In [1] based on the R-D model some α values are presented to simplify the calculation of the AC degradation factor in terms of the signal probability (Table 1). In [1,21,22,32,33], similar approach is used to incorporate the impact of signal probability in analysis. Fig.…”
Section: Nbti and Pbti Modelsmentioning
confidence: 99%